Taras Shevchenko in image strategies of modern Ukraine: linguistic argumentation - Pliasun, Olha (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article concentrates on important issues of linguistic imageology – a new direction in the humanities which investigates linguistic peculiarities of image creation. Current research is focused on studying linguistic aspects of image formation in modern mass media which can be done within the framework of an innovative humanitarian discipline – medialinguistic imageology. This newly discovered linguistic branch analyses both linguistic and extralinguistic characteristics of image shaping. Exploring the conceptual apparatus of medialinguistic imageology, the author reveals that a great deal of its notions is of integral nature, i.e. they were borrowed in science from military and political terminology systems. Simultaneously, new concepts in this field are constantly being developed. One of such brand new notions in medialinguistic imageology are concepts “image strategy” and “image strategy of a state”.  The author aims to give a comprehensive analysis of these notions  in media linguistics. The main objective of the paper is to explore linguistic factors of  formation of Ukraine’s national and international image in contemporary mass media. Content analysis of recent publications about Ukraine conducted by the researcher clearly indicates that precedent names of culture play a critical role in the process of creating the image of the state in media. Such prominent figures as Yaroslav the Wise, Bohdan Khmelnytsky, Grigory Skovoroda, Taras Shevchenko etc. are regarded as cultural markers of the country. They are perceived by recipients as certain symbols that form the idea of the Ukrainian culture. The data obtained clearly show that precedent proper name Taras Schevchenko is an essential part of Ukraine’s image campaign, within which the author emphasizes a number of image strategies (i.e. the strategy of universal image, target image strategy, “positioning” strategy, “mythologization” strategy, “emotionalization” strategy, “visualization” strategy, “creative explosion” strategy etc.). The results of the author’s research convince that the appeal to Kobzar as Ukraine’s “business card” can be quite effective in the framework of the Ukrainian image campaign. The findings are of direct practical relevance.
Keywords: linguistic imageology, image, image of Ukraine in media, image strategy, precedent name, Taras Schevchenko.